Diagnostic Approach of Abnormal Uterine Bleeding - Kurniawan, Riyan H. (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To introduce and apply PALM-COEIN classification system as standard diagnostic approach of AUB to investigate the etiology. Method: Three cases will be discussed. First, Mrs, 45 yo, P3 with AUB due to suspected adenomiosis, performed total hysterectomy with histopathology result leiomyoma. Second case. Mrs, 43 yo, P3 with AUB due to suspected adenomiosis, performed total hysterectomy with histopathology result adenomyoma. Third case, Mrs, 48 yo, P3 with AUB due to suspected adenomiosis, performed total hysterectomy and bilateral salpingoophorectomy with PA result adenomyosis. Result: AUB diagnostic approach with PALM-COEIN performed to look for etiology and prevent mistake of etiology of AUB, such as cancer that must be consider on AUB patient above 40 years old. Conclusion: This PALM-COEIN classification should become standard diagnostic approach to investigate the etiology. [Indones J Obstet Gynecol 2014; 2: 106-109] Keywords: abnormal uterine bleeding